Optimizing the Role of E-Learning in Improving the Quality of Distance Learning at Wiralodra University - Siti Khotimah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
E-learning has become a vital component of the modern education system, driven by the rapid advancement of information and communication technology. The development of e-learning has transformed from a teacher-centered model in the 1990s to a student-centered model integrated with a Learning Management System (LMS) and advanced technologies such as Augmented Reality (AR) and Virtual Reality (VR). This study aims to analyze the historical development of e-learning, compare its implementation at the Elementary School (SD) and Higher Education (PT) levels, and evaluate its strengths and weaknesses. The final objective is to formulate a strategy to optimize the role of e-learning in improving the quality of Distance Learning (PJJ) at Wiralodra University. This study uses a qualitative approach with a descriptive analytical type. Data were obtained through literature studies and conceptual reviews of various related academic documents and references. Data analysis techniques include qualitative content analysis and comparative analysis to examine differences in learning characteristics at both levels of education and formulate strategic solutions. The implementation of e-learning in Higher Education requires independent learning and presents more complex material than in Elementary School. Although e-learning offers advantages such as easy access and the use of diverse media, several disadvantages have been identified, including excessive workloads, difficulty understanding the material, and a lack of social interaction among students. To optimize the role of e-learning at Wiralodra University, a comprehensive strategy is recommended. This strategy includes developing an integrated e-learning platform, digital literacy training for lecturers and students, building industry collaborations, providing adequate internet access, and managing a balanced workload to enhance learning effectiveness.